Vaccination of Mice with Virulence-Associated Protein G (VapG) Antigen Confers Partial Protection against Rhodococcus equi Infection through Induced Humoral Immunity - Trevisani, Marcel M.; Hanna, Ebert S.; Oliveira, Aline F.; Cardoso, Silvia A.; Roque-Barreira, Maria C.; Soares, Sandro G. (Frontiers in Microbiology, 2017)
Rhodococcus equi is a facultative intracellular bacterium causing severe pyogranulomatous pneumonia, ulcerative enterocolitis, and mesenteric lymphadenopathy in foals aged less than six months. Less frequently, this pathogen affects various other species, such as pigs, cattle, cats, and even humans. Although rhodococcosis is treated with a combination of antimicrobial agents, resistance is developed in some cases, and thus, antimicrobial susceptibility must be monitored and managed. Considering these limitations of the current therapy and unavailability of a vaccine to prevent the disease, research is particularly focused on the development of an effective vaccine against rhodococcosis. Most vaccines undergoing development utilize the virulence-associated protein (Vap) A antigen, which was identified previously as a key virulence factor of R. equi. Nevertheless, other proteins, such as VapG, present in most virulent R. equi strains, are also encoded by vap genes located on the R. equi bacterial virulence plasmid. In the present study, we evaluated the effect of VapG immunization on the survival of R. equi-challenged mice. We used attenuated Salmonella as a carrier for VapG (Salmonella-VapG+), a procedure previously adopted to develop a VapA-based vaccine. We observed that vaccination with Salmonella-VapG+ induced both an increased IFN-γ, IL-12, and TNF-α production, and a decreased bacterial burden in organs of the R. equi-challenged mice. Nevertheless, Salmonella-VapG+ vaccination protected only 50% of the mice challenged with a lethal dose of R. equi. Interestingly, we observed an increased frequency of B cells in the spleen of Salmonella-VapG+-vaccinated mice and showed that Salmonella-VapG+-vaccinated R. equi-challenged B-cell-knockout mice did not reduce the bacterial burden. Given these results, we discussed the potential role of the humoral immune response induced by Salmonella-VapG+ vaccination in conferring protection against R. equi infection, as well as the employment of VapG antigen for obtaining hyperimmune plasma to prevent rhodoccocosis in young foals.